Low-level laser irradiation induces a transcriptional myotube-like profile in C2C12 myoblasts - Ferreira, Juarez H. [UNESP]; Cury, Sarah S. [UNESP]; Vechetti-Júnior, Ivan J. [UNESP]; Fernandez, Geysson J. [UNESP]; Moraes, Leonardo N. [UNESP]; Alves, Carlos A. B. [UNESP]; Freire, Paula P. [UNESP]; Freitas, Carlos E. A.; Dal-Pai-Silva, Maeli [UNESP]; Carvalho, Robson F. [UNESP] (Springer Nature, 2018)
Low-level laser irradiation (LLLI) has been used as a non-invasive method to improve muscular regeneration capability. However, the molecular mechanisms by which LLLI exerts these effects remain largely unknown. Here, we described global gene expression profiling analysis in C2C12 myoblasts after LLLI that identified 514 differentially expressed genes (DEG). Gene ontology and pathway analysis of the DEG revealed transcripts among categories related to cell cycle, ribosome biogenesis, response to stress, cell migration, and cell proliferation. We further intersected the DEG in C2C12 myoblasts after LLLI with publicly available transcriptomes data from myogenic differentiation studies (myoblasts vs myotube) to identify transcripts with potential effects on myogenesis. This analysis revealed 42 DEG between myoblasts and myotube that intersect with altered genes in myoblasts after LLLI. Next, we performed a hierarchical cluster analysis with this set of shared transcripts that showed that LLLI myoblasts have a myotube-like profile, clustering away from the myoblast profile. The myotube-like transcriptional profile of LLLI myoblasts was further confirmed globally considering all the transcripts detected in C2C12 myoblasts after LLLI, by bi-dimensional clustering with myotubes transcriptional profiles, and by the comparison with 154 gene sets derived from previous published in vitro omics data. In conclusion, we demonstrate for the first time that LLLI regulates a set of mRNAs that control myoblast proliferation and differentiation into myotubes. Importantly, this set of mRNAs revealed a myotube-like transcriptional profile in LLLI myoblasts and provide new insights to the understanding of the molecular mechanisms underlying the effects of LLLI on skeletal muscle cells.
Keywords: Laser treatment; Muscle regeneration; Myogenesis; RNA sequencing; Transcriptome